Синантропная флора долины реки Рось и ее анализ - Куземко, А.А. (Промышленная ботаника, 2003)
The composition of the synanthropic flora of the Ros’ river valley (The Rihgt-Side Steppe-Forest Zone) has been studied, and the conspect has been presented. The 358 synantropic species have been numbered in the valley. The analysis conducted determined quantitative prevalence of the apophyte fraction comparative with adventive fraction, and main role of hemiapophytes and accidental apophytes in the apophyte fraction; predominance of the archeophytes compared with kenophytes, the considerable participation of the agriophytes and ergaziophytes in the adventive fraction. The dominant status of the mesohemerobes has been determined. Correlation of the apophytizm and naturalization indications is the 1/1,14 with the profit for the last. A conclusion concerning the valley’s flora keeps the features typical for a little disturbed nature floras was made.